Economic impacts of commercializing insect-resistant GM maize in China. Issue 3 (4th September 2017) - Xie, Wei; Ali, Tariq; Cui, Qi; Huang, Jikun
Abstract : Purpose: The purpose of this paper is to examine the potential economic impacts of China's insect-resistant GM maize and provide new evidence for decision making concerning its commercialization. Design/methodology/approach: This study uses data drawn from the production trials of insect-resistant GM maize and expert interviews to determine the impacts of commercializing GM maize at farm level under three scenarios with varying severity of insect pest attacks in maize production. Economic impacts are simulated using a modified Global Trade Analysis Project model. Findings: In farm terms, insect-resistant GM maize increases crop yield and reduces both pesticide and labor inputs. In national terms, China can increase its GDP by USD8.6 billion and maize self-sufficiency by about 2 percent given normal insect pest attacks if China commercializes GM maize. Additional beneficiaries include consumers and the livestock industry. Non-maize crops can also benefit from land saving through GM maize commercialization. Chemical is a sector with the decrease in its output because demand for pesticides will fall. Originality/value: Although China has announced a roadmap for commercializing GM crops for use as feed and in processing after nearly two decades of producing GM cotton, no clear timetable for producing GM maize as feed has been established due to several concerns, including the potential for economic gains from GM maize. This study is the first to assess the economic impacts of commercializing China's GM maize. The findings should have significant policy implications for the development and commercialization of GM crops in general and GM maize in particular.